Discovery of natural flavonoids as activators of Nrf2-mediated defense system: Structure-activity relationship and inhibition of intracellular oxidative insults. Issue 18 (1st October 2018) - Li, Yan-Ru; Li, Guo-Hui; Zhou, Ming-Xing; Xiang, Lan; Ren, Dong-Mei; Lou, Hong-Xiang; Wang, Xiao-Ning; Shen, Tao
Graphical abstract: Abstract: Continuous overproduction of reactive oxygen species (ROS), termed as oxidative stress, plays a crucial role in the onset and progression of many human diseases. Activation of nuclear transcription factor erythroid 2-related factor (Nrf2) by small molecules could eliminate ROS, and thus block the pathogenesis of oxidative stress-induced diseases. In this study, a natural flavonoid library was established and tested for their potential Nrf2 inducing effects. Based on QR inducing effect of flavonoids, their structure-activity relationship (SAR) on Nrf2 induction was summarized, and twenty flavonoids were firstly identified to be potential activators of Nrf2-mediated defensive response. Then, 7- O -methylbiochanin A (7-MBA) was further investigated for its capability on the Nrf2 activation and prevention against oxidative insults in human lung epithelial cells. Further studies indicated that 7-MBA activated Nrf2 signaling pathway and protected human lung epithelial Beas-2B cells against sodium arsenite [As(III)]-induced cytotoxicity in an Nrf2-dependent manner. Activation of Nrf2 by 7-MBA upregulated intracellular antioxidant capacity, which was produced by enhancement of Nrf2 stabilization, blockage of Nrf2 ubiquitination, as well as Nrf2 phosphorylation by mitogen-activated protein kinase (MAPK), protein kinase C (PKC), protein kinase R-like endoplasmic reticulum kinase (PERK), and phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K). Taken together, 7-MBA is a novel isoflavone-type Nrf2 activator displaying potential preventive effect against oxidative damages in human lung epithelial cells.